2016
DOI: 10.1016/j.ijid.2015.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Single- and multiple-dose pharmacokinetics of ethambutol and rifampicin in a tuberculosis patient with acute respiratory distress syndrome undergoing extended daily dialysis and ECMO treatment

Abstract: The dosing of drugs in critically ill patients undergoing renal replacement therapy is based on limited data. We report for the first time single- and multiple-dose pharmacokinetics of ethambutol (EMB), which is cleared renally to 80%, and rifampicin (RIF), which is cleared renally to <30%, in a patient requiring both extracorporeal membrane oxygenation (ECMO) and renal replacement therapy. Extended dialysis removed a considerable amount of both EMB and RIF, with a dialyser plasma clearance ranging between 37 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…The available studies have shown significant variability, suggesting the importance of therapeutic drug monitoring (TDM). One case report showed that extended dialysis in an ECMO patient effectively eliminates ethambutol, and rifampicin could also be found in the spent dialysate, despite previous reports indicating that it is not dialysable . In a matched cohort study with 5 patients receiving RRT and ECMO and 6 patients receiving ECMO only, variation in meropenem clearance was correlated with presence of RRT .…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…The available studies have shown significant variability, suggesting the importance of therapeutic drug monitoring (TDM). One case report showed that extended dialysis in an ECMO patient effectively eliminates ethambutol, and rifampicin could also be found in the spent dialysate, despite previous reports indicating that it is not dialysable . In a matched cohort study with 5 patients receiving RRT and ECMO and 6 patients receiving ECMO only, variation in meropenem clearance was correlated with presence of RRT .…”
Section: Resultsmentioning
confidence: 96%
“…Because these drugs are cleared by extended dialysis, the impact of ECMO is difficult to assess. However, the removal of ethambutol and rifampicin by the ECMO membrane was not detected when pre‐ and post‐ECMO filter levels were measured . In another case report, the plasma concentration of rifampicin was below the therapeutic level, despite the use of a higher dose (750 mg) than is recommended (600 mg) .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Ethambutol doses between 1000-2000 mg/day are suggested for patients on renal replacement therapy to achieve target peak levels. 100 These conflicting data supports the use of therapeutic drug monitoring in ECMO patients to ensure target concentrations.…”
Section: Antituberculosis Agentsmentioning
confidence: 99%